Colds, flu and coughing: A review of over-the-counter nasal therapies in general practice - J. van Schoor (South African Family Practice)
Nasal congestion due to the common cold occurs because of dilation of the blood vessels, leading to swelling of the nasal mucosal epithelium. This narrows nasal passages, which are further blocked by increased mucus production. Nasal sprays and drops are often recommended for the treatment of rhinorrhoea and nasal congestion associated with the common cold. This brief review discusses over-the-counter nasal therapies that are used to relieve rhinorrhoea and nasal congestion in adults and children.